2009
DOI: 10.2478/v10009-009-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of copper and zinc on biomass and taxonomic composition of algal periphyton communities from the River Gharasou, Western Iran

Abstract: Indoor artificial streams were used to evaluate the short-term (24 day) influence of copper and zinc, individually and in combination, on the biomass and taxonomic composition of algal periphyton communities. The effects of Cu (50 µg l -1 ) and Zn (1 mg l -1 ) were assessed using measurements of biomass, ash-free dry mass (AFDM), chlorophyll-a concentration, taxonomic composition and biovolume. In artificial streams with Cu, Zn and Cu+Zn, there were significant (p < 0.05) reductions of chlorophyll-a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Exposure to chromium -at the concentration tested and during a short-term period (i.e., 96 h) -would therefore appear not to have affected the algal biomass or the density of the mature biofilms (those having various growth forms: adnates along with stalked and motile species) in this experiment. In contrast, different authors have reported a decrease in algal biomass related to longer exposures to copper, zinc, and/or cadmium -i.e., from 24 days to 2-12 weeks (Atazadeh et al, 2009;Ivorra, 2000;Morin et al, 2012;Paulsson et al, 2000;Serra and Guasch, 2009;Soldo and Behra, 2000). In agreement with the results here, Duong et al (2010) reported that a mature biofilm's development was not inhibited after two weeks of cadmium contamination and seemed to be more resistant to cadmium toxicity, unlike the significant decrease in biomass they observed in younger biofilms.…”
Section: Discussionsupporting
confidence: 82%
“…Exposure to chromium -at the concentration tested and during a short-term period (i.e., 96 h) -would therefore appear not to have affected the algal biomass or the density of the mature biofilms (those having various growth forms: adnates along with stalked and motile species) in this experiment. In contrast, different authors have reported a decrease in algal biomass related to longer exposures to copper, zinc, and/or cadmium -i.e., from 24 days to 2-12 weeks (Atazadeh et al, 2009;Ivorra, 2000;Morin et al, 2012;Paulsson et al, 2000;Serra and Guasch, 2009;Soldo and Behra, 2000). In agreement with the results here, Duong et al (2010) reported that a mature biofilm's development was not inhibited after two weeks of cadmium contamination and seemed to be more resistant to cadmium toxicity, unlike the significant decrease in biomass they observed in younger biofilms.…”
Section: Discussionsupporting
confidence: 82%
“…The structure of diatom communities may also be affected by elevated levels of inorganic chemicals in addition to natural resources (Deniseger et al 1986;Gray and Hill 1995;Genter 1996;Paulsson et al 2000;Atazadeh et al 2009). In the present study, the susceptibility of diatoms to metals is reported in Fig.…”
Section: Diatom Communitymentioning
confidence: 99%
“…In situ measurements of temperature, pH, electrical conductivity, turbidity, depth, oxidation reduction potential, and dissolved oxygen were obtained using an Horiba multimeter (Water checker U-52G). Then, samples collected for water quality analyses were filtered using 0.45 µm syringe filters at each site for total suspended solids, total dissolved solids, total oxidised nitrogen, total phosphorous, total nitrogen, ammonia, silica, cations and anions were undertaken in the laboratory at Federation University Australia using a spectrophotometer and Gallery Automated Photometric Analyser and Hach DR 2800 following standard methods (APHA 2007, Atazadeh et al 2009, Victoria EPA 2009.…”
Section: Methodsmentioning
confidence: 99%